MEDIA BANTU PEMBELAJARAN IPA SMP SEBAGAI BEKAL MENGHADAPI UJIAN NASIONAL (UN) - Muhammad Hairul Abror; Dadang Priyanto (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2015)
Ujian National (UN ) is one tool evaluation issued by the government which is the appropriate measurement tool to measure the level of achievement of educational goals that have been set. One of the challenges for students of schools during the school beforehand through the UN process be it elementary, junior high and high school. As is known, to fnish his previous students have to face the evaluation process, namely Ujian Nasional, and to pass the evaluation of the value of the good is not easy. That requires a media that can help students in the learning process before the Ujian National. Media made using multimedia elements such as text, images, sound, and animation. The development method used by the authors in this study is the method ADDIE which has fve stages, namely stage Analysis, Design, Development, Implementation, and Evaluation. The instructional media of Natural Science for Yunior School to prepare UN â€ From the results obtained during this study, the authors conclude that the media are built to help students in the learning process before facing Ujian National (UN)